MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE LATIHAN SIAP SISWA KELAS I B SD NEGERI 006 TERPADU KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Hasna Wirdati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
The background of this research is the low of mathematics learning result of first grade student of SD Negeri 006 Terpadu Kubang Jaya. This is evidenced by the average of student learning outcomes is equal to 45.25 with good enough category, besides the total number of completed students is 13 students or 32.50%. Based on the result of the low learning result, the researcher conducted the class action research activity, by applying the learning method of the training ready to improve the students' mathematics learning outcomes. This research was conducted at SD Negeri 006 Terpadu Kubang Jaya, the subject of this research is the students of class I with the number of students 40. The stages of this research consist of four stages: planning, implementation, observation, and reflection. This research was conducted two cycles. Data retrieval technique used is a test technique. The result of research indicated that after doing the action by applying the method of learning practice of learning to increase, in cycle I the total number of complete students is 13 students (32.50%) the average of the related learning outcomes is 61.25 with good category. In cycle II the number of completed students increased to 37 students (92,50%) with average value of learning value equal to 81,50 with very good category. Based on the results of learning on the second cycle of student learning outcomes that have been completed because of the classical completeness of students has reached 80.00.